Dynamic consistency in incomplete information games with multiple priors - Marieke Pahlke (Bielefeld University, Center for Mathematical Economics (IMW), 2018)
This paper generalizes the concept of Sequential Equilibrium to allow for ambiguous incomplete information about types or states. We characterize conditions that ensure existence of Sequential Equilibria under ambiguous incomplete information. Under these conditions players form subjective prior belief sets that satisfy a rectangularity condition which leads to dynamically consistent behavior. Furthermore, we give an example which shows that ambiguity can introduce new Sequential Equilibria.
urn:nbn:de:0070-pub-29304923
Keywords: C73; D81; 330; sequential equilibrium; ambiguity; dynamic consistency; multiple priors; imprecise information